The Art of Leadership (Audio Book) - Lopp, Michael (O'Reilly Media, Inc., 2020)
Many people think leadership is a higher calling that resides exclusively with managers who practice or follow big compelling leadership philosophies. But what's most important for leadership is principled consistency, because small things done well time and again without fail build trust and respect within a team. Using stories from his time at Netflix, Apple, and Slack, Michael Lopp presents a series of practices to help you build leadership skills. You'll learn how to create teams that are highly productive, highly respected, and highly trusted. Lopp has been speaking and writing about this topic for over a decade. He maintains a Slack channel with nearly 12000 members. In this practical audio book, Lopp illustrates the leadership skills he learned from exceptional leaders at three dynamic companies: Act I: As a manager under James Barksdale at Netflix Act II: As a senior manager/director under Steve Jobs at Apple Act III: As an executive with Stewart Butterfield at Slack.
Online resource; Title from title page (viewed June 26, 2020)